Itinerário terapêutico de mães de crianças que foram a óbito no período neonatal em município do interior paulista - Santiloni, Aline Fernanda Palombarini [UNESP] (2015)
Infant mortality rates are configured as indicators expressing the living conditions and health of the population, since they are determined mainly by socioeconomic conditions and the quality of the obtained health care. From the second half of the 90s of the twentieth century, it was observed that the neonatal mortality rate, which was around 20 deaths / thousand live births, now accounts for 60% of deaths in children under one year. It was intended, with this study, the analysis of the therapeutic road traveled by mothers of children who died from preventable causes in the neonatal period, from January 2013 to June 2014 at a university hospital in São Paulo. This qualitative nature study was developed based on the framework of therapeutic itinerary, based on the narratives of mothers of children who died in the neonatal period. Semi-structured interviews with nine women were interviewed. The collected material was systematized according to the Content thematic analysis method, being subdivided into categories: Prenatal Care,Childbirth Care and Postpartum Care of the Mother and Newborn. It was observed that the active search for the best care for women was constant in the three times, and the devolutiva service, both public and private, across the health needs presented, demonstrated weaknesses, distancing themselves from the principles and guidelines established by the SUS . We emphasize the importance of investments in early detection and its front conducts the complications presented by pregnant women, pregnant women, mothers and newborns, valuing and ensuring the proper care of the demands presented